Soluble Programmed Death 1 (PD-1) Is Decreased in Patients With Immune Thrombocytopenia (ITP): Potential Involvement of PD-1 Pathway in ITP Immunopathogenesis. (April 2016) - Birtas Atesoglu, Elif; Tarkun, Pinar; Demirsoy, Esra Terzi; Geduk, Ayfer; Mehtap, Ozgur; Batman, Adnan; Kaya, Fatih; Cekmen, Mustafa Baki; Gulbas, Zafer; Hacıhanefioglu, Abdullah
Immune thrombocytopenia (ITP) is an autoimmune disease characterized by dysregulation of T cells. Programmed death (PD) 1 and programmed death 1 ligand 1 (PD-L1) are cosignaling molecules, and the major role of the PD-1 pathway is the inhibition of self-reactive T cells and to protect against autoimmune diseases. We measured levels of serum soluble PD 1 (sPD-1) and serum soluble PD-L1 (sPD-L1) in 67 patients with ITP (24 newly diagnosed ITP [ndITP], 43 chronic ITP [cITP]) and 21 healthy controls (HCs). We determined decreased serum sPD-1 levels both in patients with ndITP and in patients with cITP when compared to HC. Moreover, there was a positive correlation between sPD-1 levels and platelet counts. The sPD-L1 levels were decreased in patients with ndITP when compared to patients with cITP. This is the first study investigating PD-1 signaling pathway in ITP. Decreased sPD-1 levels may have a role in ITP pathogenesis as without the inhibitory regulation of PD-1, sustained activation of T cells may cause inflammatory responses which is the case in ITP.